The Strongholds of Corsica between revolt, civil war and the War of the Austrian Succession (1740-1748) - Beri, Emiliano (Cuadernos de Historia Moderna, 2022)
Under the name “Corsician wars” should be understood an almost uninterrupted sequence of uprisings against the Republic of Genoa covering the central forty years of the 18th century (1729-1768). Genoa was able to cope with this long conflict mainly by retaining control of Bastia, Calvi, Ajaccio and Bonifacio. The conflict led to radical changes in the configuration of these four cities, which were particularly evident during the years of the War of the Austrian Succession (1740-1748). These changes affected the exercise of power, institutional architecture, the defense system and the military function
Keywords: Strongholds; citadel; military function; projection of force; shelter